MANGROVE FOREST CONDITION IN PIRU BAY, WEST SERAM, MOLUCCAS - Fasmi Ahmad (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2015)
Information on condition and biodiversity of mangrove ecosystem to support a sustainable management of mangrove ecosystem is very important in the coastal region of Eti village, Piru Bay, West Seram, Molluccas. The purposes of this study were to determine the condition and biodiversity of mangrove ecosystem in the village of Eti, Gulf Piru. Filed data collection was conducted in November 2010 using the line transect method. The box size along the transects was made in accordance with its purposes such as 10 x 10 m2 for trees, 5 x 5 m2 for sapling, and 1 x 1 m2 for seed. The distance between the box transect was 25 m. Number of individuals of each species were counted and the diameter at the chest-height was also measured. Results showed that sixteen species were found within ten genera. There were 9 species of tree categories, 10 species of sapling categories, and 8 species of seed categories. The highest density and frequency of occurrence for the three categories was represented by Rhizophora apiculata, while the largest coverage percentage was represented by Sonneratia alba. The highest important value was also represented by Rhizophora apiculata. In general, the condition of mangrove forests in the village of Eti, Piru Bay was still relatively good, but the local community was very active to take advantage of these mangrove forests products such as charcoal, fencing, and wood that they sold every week. Therfore, it is necessary for local government efforts to protect the mangrove ecosystem from destructed activities of the local community.Keywords: mangrove forest, Rhizophora apiculata, Sonneratia alba, Teluk Piru, Molluucas